Growth and sexual development of Etawah-cross kids from does of different levels of milk production - Sutama, I-Ketut; Budiarsana, I-G.M; Mathius, I-Wayan; Juarini, E (Indonesian Animal Sciences Society, 1999)
The experiment was conducted to evaluate growth and sexual development of female Etawah-cross kids of the progeny of the does with low (Group L), medium (Group M) and high (Group H) milk production. The does were fed King grass (Pennisetum purpureophoides) (about 2% DM of liveweight) and 400 g/head of concentrate. The amount of concentrate was increased to 600 g/head during the last two months of pregnancy period and during lactation. Kids were weaned at four months of age. Thereafter, they were reared in group and were fed King grass and concentrate. The animals were weighed every two weeks. A mature vasectomized buck were joined in each group to detect the onset of first oestrus (puberty). When kids reached puberty and had a liveweight of about 20 kg, they were mated with intact buck. Ovulation rate, progesterone profiles and fertility were observed. The results showed that pre-weaning growth rates of kids in all three groups were not significantly different (67.0 vs 74.9 vs 70.5 g/day, P>0.05). At six and 12 months of ages, Groups L and M had almost the same liveweight which were higher than Group H. Consequently, Groups L and M reached puberty about 3 - 6 weeks earlier than Group H. The average liveweight at puberty was 19.9, 18.2 and 18.8 kg for Groups L, M and H, respectively, or at about 57.1-69.8% (average 63.2%) of mature liveweight. The pregnancy rate following first mating was relatively high (67-73%) and all does were pregnant in the following mating. Average ovulation rate at conception were low (1.1) in all groups. It was concluded that differences in milk production of the does did not significantly affect post-weaning growth and sexual development and performances of kids. Other factors at certain age or growth phases might be more important to affect growth and reproduction of Etawah-cross goat, and this may warrant further study. Â Key words : Growth, reproduction, Etawah-cross does